Cytokine patterns in critically ill patients undergoing percutaneous tracheostomy. (20th June 2019) - Trahtemberg, U; Bazak, N; Sviri, S; Beil, M; Paschke, S; van Heerden, PV
Summary: The inflammatory response to acute injury among humans has proved difficult to study due to the significant heterogeneity encountered in actual patients. We set out to characterize the immune response to a model injury with reduced heterogeneity, a tracheostomy, among stable critical care patients, using a broad cytokine panel and clinical data. Twenty-three critical care patients undergoing percutaneous bedside tracheostomies were recruited in a medical intensive care unit. Blood samples were collected at five intervals during 24-h peri-procedure. Patients were followed-up for 28 days for clinical outcomes. There were no statistically significant changes in any of the cytokines between the five time-points when studied as a whole cohort. Longitudinal analysis of the cytokine patterns at the individual patient level with a clustering algorithm showed that, notwithstanding the significant heterogeneity observed, the patients' cytokine responses can be classified into three broad patterns that show increasing, decreasing or no major changes from the baseline. This analytical approach also showed statistically significant associations between cytokines, with those most likely to be associated being interleukin (IL)-6, granulocyte colony-stimulating factor (GCSF) and ferritin, as well as a strong tri-way correlation between GCSF, monocyte chemoattractant protein 1 (MCP1) and macrophage inflammatory protein-1β (MIP1β). In conclusion, in this standard human model of soft tissue injury, by applying longitudinal analysis at the individual level, we have been able to identify the cytokine patterns underlying the seemingly random, heterogeneous patient responses. We have also identified consistent cytokine interactions suggesting that IL-6, GCSF, MCP1 and MIP1β are the cytokines most probably driving the immune response to this injury. Graphical Abstract: